El Dr. Alcina y los códices mesoamericanos - Batalla Rosado, Juan José; De Rojas, José Luís (Revista Española de Antropología Americana, 2003)
Among the extensive bibliographical production of Dr. Alcina, there are some studies about the Mesoamerican codices. This paper deals about them. We present the results of the researching of D. José and highlight the significance of his work.